Resident’s Perspective on Developing Community-Based Tourism – A Qualitative Study of Muen Ngoen Kong Community, Chiang Mai, Thailand - Lo, Yu-Chih; Janta, Pidpong (Frontiers in Psychology, 2020)
Community-Based Tourism (CBT) has been presented as an alternative to sustain tourism development in developing countries. This tourism model offers local residents an opportunity to manage natural and cultural resources in order to promote local economy and generate greater benefits. The objective of the study is to investigate the benefits, challenges of CBT and solution to address identified shortcomings by studying Muen Ngoen Kong community in Chiang Mai, Thailand. In order to achieve these objectives, qualitative methods; field observation and interview were employed and qualitative data were analyzed by thematic analysis. The results of field observation and interview data from local residents were reported, analyzed, and discussed. To practice CBT, the findings indicated that several challenges; conflict over resource ownership and benefit leaking, financial issues, and problems of community participation had been experienced in implementation of CBT. However, abundance of tourism resources and security related concerns were identified as benefits of CBT in the area. In close collaboration with government agency, product development was recommended to create a unique condition for CBT and address shortcoming. It is crucial to involve local residents, empower the local community, conserve and cultivate cultural resources, and finally, maintain the sustainability of overall tourism resources.